FACTORS AFFECTING PURCHASE INTENTION OF NU GREEN TEA PRODUCT IN JABODETABEK - Maris Agung Triandewo; Sherviana Sherviana (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The purpose of this research is to identify whether Brand Ambassador, E-WOM Quality, E-WOM Quantity, and Sender's Expertise have influenced on consumer Purchase Intention on Nu Green Tea products in Jabodetabek. The population used in this study is people who live in Jabodetabek who have never bought Nu Green Tea. The method used to conduct this research is purposive sampling method. The sample used in this study was 137 respondents. The statistical method used is multiple regression analysis to test the hypothesis of the variables in this study. The results of this study showed that Brand Ambassador and Sender's Expertise have influenced on Purchase Intention. Meanwhile, E-WOM Quality and E-WOM Quantity have no effect on Purchase Intention